Preparation and Evaluation of pH Sensitive Novel Anticancer Drug Carrier Based on Magnetic Chitosan Quartets - Danafar, Hossein; Asadi, Farnaz; Sharafi, Ali; Manjili, Hamidreza Kheiri (Drug Research, 2019)
Chitosan-coated magnetic nanoparticles are an appropriate drug delivery method which can improve the therapeutic properties of chemotherapy agents and also can be useful as MRI contrast agent for early cancer diagnosis. This research discovers the optimization of the possible therapeutic effects of Chitosan- citric acid- Fe3O4- CUR quartets. Chitosan as a natural polymer can use to encapsulate citric acid modified Fe3O4 nanoparticles. The successful preparation of CUR-loaded nano-carriers was confirmed by X-ray diffraction (XRD), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FTIR), vibrating sample magnetometer (VSM) and transmission electron microscopy (TEM) techniques. Moreover, the hemolysis test was used for the study of hemobiocompatibility. The loading capacity and encapsulation efficiency of CUR molecules were 11±0.09% and 49.5±0.41%, respectively. The anticancer effect of the void of CUR and CUR-loaded nano-carriers were compared by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay on the treated MCF-7 cell lines. It can be concluded that the use of these nanoparticles are a better and more efficient approach for the controlled and slow release of CUR in the cancer treatment.
Keywords: chitosan; citric acid; drug delivery; curcumin; magnetic nanoparticles